Estimates of logarithmic coefficients of univalent functions - Stephen M. Zemyan (International Journal of Mathematics and Mathematical Sciences)
In this paper, we derive some consequences of Milin's inequallty for the logarithmic coefficients of a univalent function by exploiting a reformulation of it.